Risk factory and prevention of urinary incontinence in women - Zydek, Cezary; Miękoś, Eugeniusz; Sosnowski, Marek (Menopause Review/Przegląd Menopauzalny, 2004)
Urinary Incontinence (UI) in women has been claimed as social disease thus its frequency has exceeded 5%. UI risk factors have been classified as urogynecological, constitutional, neurological and behavioral. Many authors consider as UI risk factors only; postmenopausal period, numerous deliveries, exhausting physical work, elevated BMI (Body Mass Index), previous minor pelvis surgery and radiotherapy. Based upon their own research as well as references the authors have classified the UI risk factors as: predisposing, inciting, promoting and decompensating. In-depth analysis of all UI risk factors allowed to recognize the disease pathogenesis, the influence of environmental, cultural, genetic and anatomic factors and to work out the prevention methods and the treatment outcomes improvement. The numerousity and low efficacy of curently used methods of UI treatment indicate the need for performing large scale research off all potential risk factors.